Energy expenditure through physical activity in a population of community-dwelling Brazilian elderly: cross-sectional evidences from the Bambuí cohort study of aging Gasto energético com atividades físicas em idosos Brasileiros residentes em comunidade: evidências do estudo de coorte de idosos de Bambuí - Juciany Rodrigues de Oliveira Ramalho; Maria Fernanda Lima-Costa; Josélia O. A. Firmo; Sérgio Viana Peixoto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to estimate physical activity energy expenditure among older adults. The study comprised 1,585 residents in Bambuí, Minas Gerais State, Brazil, aged > 60 years (91% of the town's total elderly), and examined the frequency and duration of 23 types of physical activity among them. Median energy expenditure was 975 MET.min/week (1,195.8 among men and 803.1 among women), declining significantly with age in both sexes. The prevalence of sedentary lifestyles (< 450 MET.min/week) was 31.2%. Unhurried walking accounted for about 1/3 of total energy expenditure. Multivariate analysis based on ordinal logistic regression showed inverse associations between energy expenditure and age and hospitalizations in both sexes. Among men, inverse associations were observed with smoking, number of chronic diseases and number of medical appointments. These results emphasize the need for effective strategies to increase physical activity in older elderly, and underscore the high prevalence of walking in this group. O objetivo deste trabalho foi estimar o gasto energético das atividades físicas entre idosos. Participaram do estudo 1.585 residentes da cidade de Bambuí, Minas Gerais, Brasil, com > 60 anos (91% da população total de idosos). Foram pesquisados 23 tipos de atividade física, sua frequência e duração. A mediana do gasto energético foi de 975,0 MET.min/semana, (1.195,8 entre homens e 803,1 entre mulheres), com acentuado declínio com a idade nos dois sexos. A prevalência do sedentarismo (< 450 MET.min/semana) foi de 31,2%. Caminhar normalmente (sem pressa) correspondeu a cerca de 1/3 do total do gasto energético estimado. Em ambos os sexos, os resultados da análise multivariada baseada na regressão logística ordinal mostraram associações inversas entre gasto energético e idade e ocorrência de hospitalizações. Entre homens, foram observadas associações inversas com tabagismo, número de doenças crônicas e consultas médicas. Esses resultados ressaltam a necessidade de estratégias efetivas para aumentar as atividades físicas de idosos mais velhos, chamando atenção para o predomínio da caminhada nesse grupo.